2021
DOI: 10.1186/s13019-021-01423-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Uniportal video-assisted thoracic surgery of bilateral pulmonary nodules

Abstract: Background Surgical resection is an appropriate treatment option for synchronous bilateral pulmonary nodules with ground-glass opacities. The applicability of simultaneous uniportal video-assisted thoracic surgery is not fully understood. We evaluated the feasibility and safety of performing such surgeries at our hospital. Methods Clinical data of 35 patients who underwent simultaneous bilateral pulmonary resection with uniportal video-assisted tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…This study is one of very few to have investigated simultaneous bilateral lung resection using VATS for indeterminate lung neoplasms. While several studies have shown the feasibility and safety of simultaneous bilateral VATS resection, such as comparisons between one-stage versus two-stage, or intercostal versus subxiphoid bilateral procedures [5][6][7][8][9][10], none have commented on the difference regarding the extent of resection in one-stage operations. In our study over a 10-year period, we assessed the clinicopathologic outcome and perioperative context of 207 patients with bilateral lung neoplasms undergoing SBTLR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is one of very few to have investigated simultaneous bilateral lung resection using VATS for indeterminate lung neoplasms. While several studies have shown the feasibility and safety of simultaneous bilateral VATS resection, such as comparisons between one-stage versus two-stage, or intercostal versus subxiphoid bilateral procedures [5][6][7][8][9][10], none have commented on the difference regarding the extent of resection in one-stage operations. In our study over a 10-year period, we assessed the clinicopathologic outcome and perioperative context of 207 patients with bilateral lung neoplasms undergoing SBTLR.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, one-stage surgery for managing a wide array of thoracic diseases is proven to be safe and efficacious [1][2][3][4][5][6][7][8][9][10]15], and its advantages include circumventing the risk of contralateral tumor progression, comparable wound pain when compared with unilateral-side surgery, decreased medical cost, and decreased psychological burden. In our study, SBTLR allowed clear pathological discrimination in patients with indeterminate lung neoplasms and produced a perioperative course with a comparable safety profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, evaluating pulmonary function inpatients who will undergo simultaneous bilateral pulmonary surgery is crucial. Previous research has demonstrated that pneumonectomy is safe if FEV1 is greater than 2L and that lobectomy is safe if it is greater than 1.5 L or if its predicted value is more than 80% ( 16 , 17 ).For simultaneous bilateral pulmonary surgery, anFEV1/forced vital capacity of more than 75% is recommended ( 18 ).It is interesting to note that female patient shave been found to have better outcomes than male patients after pulmonary surgery, which may be caused by their smaller vital capacity ( 19 ).…”
Section: Discussionmentioning
confidence: 99%